2х(х+ 3)^2 - 3х(х- 1)(х+ 8) -3х(2 -3х) help

Podokonik Podokonik    1   08.04.2020 00:54    0

Ответы
AkvaH2O AkvaH2O  06.08.2020 19:30

-x^3+36x

Пошаговое объяснение:

2x(x+ 3)^2 - 3x(x- 1)(x+ 8) -3x(2-3x) = 2x(x^2+6x+9) - 3x(x^2 + 8x - x - 8) - 6x +\\\\ 9x^2 = 2x^3 + 12x^2 + 18x - 3x^3 - 21x^2 + 24x - 6x + 9x^2 = -x^3 + 36x

ПОКАЗАТЬ ОТВЕТЫ
котёнок130 котёнок130  06.08.2020 19:30

2х(х²+6х+9)-3х(х²+8х-х-8)-6х+9х²=2х³+12х²+18х-3х³-24х²+3х²+24х-6х+9х²=-х³+36х

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика